Eufemisme dan Disfemisme dalam “Surat Terbuka Kepada DPR-RI” Narasi TV: Tinjauan Semantik - Icha Fadhilasari; Gita Rosarum Ningtyas (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Euphemisms and dysfemisms are often used as journalism rhetoric for public broadcast/content. This cannot be separated from the role of the mass media as an information institution for all segments. In that case, euphemisms and dysfemisms become expressions to offend and overthrow certain parties deemed to be detrimental to society. This research is motivated by the dominant use of euphemisms and dysfemisms in the video entitled